Health and school difficulties of children in foster care in the experience of their foster parents - Faltová, B.; Mojžíšová, A.; Holá, J.; Shuranová , L.; Čermák, Z. (Medicni Perspektivi, 2024)
The period of compulsory school attendance is a mentally very challenging period for children in foster care, which can be impacted by complex developmental trauma stemming from the child's experience in foster care with cumulative and chronic traumatic events in his/her biological family. These events have taken place over a long period of time in interpersonal relationships usually related to caregivers, in the form of abandonment of the child by the caregiver, changing caregivers, lack of safe space and necessary support for the child from the family and school, and/or deficiencies in the provision of coordinated health and social care for both the child and the foster parents. The paper presents research findings supported by a statistical analysis of health and school difficulties in children in foster care related to their school attendance. The purpose of the research was to support the quality and coordination of services of non-profit organizations providing social, health and educational services to foster families and their children during school attendance to support the school success and well-being of children. The study was implemented as part of a dissertation at the University of South Bohemia in České Budějovice in the Czech Republic on the topic of promotion of the health, social and psychological well-being of school-aged children in the context of their school and family environment. The authors carried out a questionnaire survey in the Czech Republic among a selected sample of respondents, who were foster parents of children aged 6 to 15 attending primary school in the Pardubice Region. In a total sample of 102 respondents, we identified two different groups. One group – 64 respondents with healthy children and another group – 38 respondents with children with health difficulties. The aim of the research was to compare the assessments of the intensity of school difficulties of children in foster care in groups of respondents with or without a child with health difficulties or mental illness in their foster care. The hypothesis of a difference in assessments of school difficulties in children with/without health difficulties was formulated and statistically tested (H0: ratings of the intensity of difficulties are the same in both groups). Statistical testing of the hypothesis utilised the non-parametric Mann-Whitney test with the test results being significant at the level of significance p<0.05. Correlation was observed for each difficulty and exploratory cluster analysis shows their interrelationships. The study results according to the foster parents' assessment show a high intensity of difficulties of school-aged children in foster care in their inclusion in the classroom in establishing relationships with classmates (p-value =0.9), in a negative attitude towards learning and lack of motivation to learn (p-value =0.7) experiencing nervousness, internal tension and staying focused when learning. In addition, when comparing the groups of respondents with healthy children and children who have health difficulties/mental illness, there was a statistically significantly higher intensity of difficulties in the group of respondents with children with health difficulties when doing prep work for the classes (p-value =0.00075).